Comparative Analysis of the Occurrence and Role of CX3CL1 (Fractalkine) and Its Receptor CX3CR1 in Hemophilic Arthropathy and Osteoarthritis - Piotr Wojdasiewicz; Łukasz A. Poniatowski; Andrzej Kotela; Marta Skoda; Michał Pyzlak; Aleksandra Stangret; Ireneusz Kotela; Dariusz Szukiewicz (Journal of Immunology Research)
Objective. Hemophilic arthropathy is characterized by recurrent bleeding episodes in patients with hemophilia leading to irreversible joint degeneration. The involvement of CX3CL1 (fractalkine) and its receptor CX3CR1 was observed in the pathogenesis of numerous arthritis-associated diseases. Taking this into account, we have presented a study investigating the role of the CX3CL1/CX3XR1 axis in the course of hemophilic arthropathy, including the CX3CL1-dependent expression of CD56+, CD68+, and CD31+ cells along with evaluation of articular cartilage and synovial membrane morphology. Methods. The study was carried out using cases (n=20) of end-stage hemophilic arthropathy with a severe type of hemophilia A and control cases (n=20) diagnosed with osteoarthritis. The biofluids including blood serum and synovial fluid were obtained intraoperatively for the evaluation of CX3CL1 using the ELISA test. Tissue specimens including articular cartilage and synovial membrane were similarly collected during surgery and stained immunohistologically using selected antibodies including anti-CX3CR1, anti-CD56, anti-CD68, and anti-CD31. Additionally, the analysis included the assessment of articular cartilage, synovial membrane, and blood vessel morphology. Results. In our study, we have documented increased average concentration of CX3CL1 in the blood serum of the study group (7.16±0.53 ng/ml) compared to the control group (5.85±0.70 ng/ml) without statistically significant difference in synovial fluid concentration at the same time. We have observed an increased macrophage presence with more marked proliferation and fibrosis of the synovial membrane in the study group. Remaining results such as expression of CX3CR1 presence of NK cells and larger surface area of blood vessels within the synovial membrane were noted also without statistical significance. Conclusions. This study has demonstrated collective CX3CL1/CX3CR1 axis involvement in hemophilic arthropathy pathogenesis introducing new interesting diagnostics and a therapeutic target.